2006
DOI: 10.1136/jcp.2006.036665
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of assessment of oestrogen receptor expression on needle core biopsy specimens of invasive carcinomas of the breast

Abstract: Aim: To assess the reliability of assessment of oestrogen receptor expression on needle core biopsy specimens of invasive carcinomas of the breast. Previous studies have mostly been small, with a range of agreement from 62% to 100%. Methods: Retrospective audit of 338 tumours surgically excised within 60 days of core biopsy, that had had oestrogen receptor assessed on both the core biopsy and tumour specimens. Surgical specimens were incised when fresh to ensure good fixation. External controls including a wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 26 publications
4
38
1
2
Order By: Relevance
“…Whereas the published literature suggests a concordance rate of 60-100% in breast samples of individual patients when core needle vs resection specimens are examined, more recent studies employing the most up-to-date methodologies in the context of larger number of cases show near 100% concordance between needle core and resection specimens. 9 However, Mann and colleagues have demonstrated that as many as 9% of women may have falsenegative ER IHC studies if their resection, rather than needle core biopsy, is utilized. These falsenegative studies may be a consequence of inadequate fixation.…”
Section: Choice Of Specimen and Fixationmentioning
confidence: 99%
“…Whereas the published literature suggests a concordance rate of 60-100% in breast samples of individual patients when core needle vs resection specimens are examined, more recent studies employing the most up-to-date methodologies in the context of larger number of cases show near 100% concordance between needle core and resection specimens. 9 However, Mann and colleagues have demonstrated that as many as 9% of women may have falsenegative ER IHC studies if their resection, rather than needle core biopsy, is utilized. These falsenegative studies may be a consequence of inadequate fixation.…”
Section: Choice Of Specimen and Fixationmentioning
confidence: 99%
“…(A) Tissue sections containing adjacent normal colonic epithelium and tumor tissue were stained for Rap1GAP as previously described (37,47). (B) Rap1GAP staining was quantified by H score (23). The H scores in tumor versus normal tissue were compared using the nonparametric Wilcoxon signed-rank test and found to be significantly different (P ϭ 0.0007).…”
Section: Fig 1 Decreased Expression Of Rap1gap In Primary Colorectalmentioning
confidence: 99%
“…1A). Semiquantitative staining according to H score (23) revealed that Rap1GAP expression was significantly decreased in tumor tissue compared to that in the adjacent normal epithelium (Fig. 1B).…”
mentioning
confidence: 99%
“…A biópsia por agulha é de particular valor para avaliação de marcadores tumorais em tumores grandes, em pacientes que vão se submeter à quimioterapia neoadjuvante. Trabalhos que avaliaram a determinação de RE na biópsia por agulha versus espécime cirúrgico mostram índice de concordância de até 98,8% (10,20) . Nos casos discrepantes, a maior positividade é obtida nas amostras de biópsia por agulha, e não nos espécimes cirúrgicos, provavelmente devido à melhor fixação tecidual que ocorre nas amostras menores e ao rápido processamento.…”
Section: Discussionunclassified
“…A expressão do RP é induzida pelo RE, por isso a maioria dos tumores RP+ também é RE+. Programas de controle de qualidade sugerem que, quando o estudo imuno-histoquímico revelar tumor RE-/RP+, deve-se repetir a análise para RE e, principalmente, melhorar a reativação antigênica (20) .…”
Section: Discussionunclassified